Transformation and Human Resource Management Strategies in Community Service Programs Based on Innovation and Collaboration to Achieve Social Welfare and Sustainable Economic Resilience - Junaidi, Ahmad; Sunarmin; Yusuf, Muhamad (PT. LITERASI SAINS NUSANTARA, 2025)
This study aims to analyze strategies for transforming and managing human resources (HR) in community service programs based on innovation and collaboration to achieve social welfare and sustainable economic resilience. The method used is a literature review with a qualitative approach on 36 selected scholarly articles from 1951–2025. The findings indicate that the effectiveness of community service programs is highly determined by HR capacity in managing social innovation, building cross-sector collaboration, and applying transformational leadership. The application of Human Capital, Transformational Leadership, Social Innovation, and Cross-Sector Collaboration theories serves as the main conceptual foundation for understanding the role of HR as agents of social and economic change. The study confirms that HR transformation strategies based on collaboration, innovation, and sustainability can enhance community independence, strengthen social networks, and create inclusive economic impacts. This research contributes to enriching the academic literature and provides strategic recommendations for higher education institutions to integrate HR management in community service with sustainability principles and results-based governance.